Psikoedukasi Untuk Meningkatkan Kepercayaan Diri Pada Remaja Broken Home di SMK Yohanes XXIII Maumere - Maria Evi Fania; Epifania Margareta Ladapase (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research aims to determine the effect of providing psychoeducation to increase self-confidence. This research uses research methods in the form of experimental data collection techniques using observation, interviews and questionnaires. This training shows an increase in self-confidence after being given psychoeducation for teenagers at SMK Yohanes XXIII Maumere. Proven by statistical analysis the value is 0.00. Because it is smaller than 0.05. So psychoeducation has a very significant influence in increasing the level of self-confidence in teenagers at SMK Yohanes XXIII Maumere.